SPIRITUAL REQUIREMENTS FOR THE LEADER (Conferencea, 2023)
The leader must be independent, able to engage in all spheres of social activity that are not prohibited by law. At the same time, he needs to be respected among the team he leads. If the leader is not active, social activity will not be formed in the society. Regardless of whether he is senior or junior, in any position, every leader asks "what should I know and what qualities should I have in order to approach my work at the required level?" the question is always cross. In management, the role of experience, skill, skill, knowledge, intelligence and perception is great. But first of all, management is art, more precisely, creativity. Talent and talent are necessary for leadership, just as it is necessary for an artist.